Efficacy, tolerability and acceptability of oxycodone for cancer-related pain in adults: an updated Cochrane systematic review. Issue 2 (13th January 2018) - Schmidt-Hansen, Mia; Bennett, Michael I; Arnold, Stephanie; Bromham, Nathan; Hilgart, Jennifer S
Abstract : Objectives: To assess the efficacy, tolerability and acceptability of oxycodone for cancer pain in adults Methods: We searched CENTRAL, MEDLINE, MEDLINE In-Process, Embase, SCI, Conference Proceedings Citation Index-Science, BIOSIS, PsycINFO and four trials registries to November 2016. Results: We included 23 randomised controlled trials with 2144 patients analysed for efficacy and 2363 for safety. Meta-analyses showed no significant differences between controlled-release (CR) and immediate-release oxycodone in pain intensity or adverse events but did show significantly better pain relief after treatment with CR morphine compared with CR oxycodone. However, sensitivity analysis did not corroborate this result. Meta-analyses of the adverse events showed a significantly lower risk of hallucinations after treatment with CR oxycodone compared with CR morphine, but no other differences. The remaining studies either compared oxycodone in various formulations or compared oxycodone to different alternative opioids. None found any clear superiority or inferiority of oxycodone in pain relief or adverse events. The quality of this evidence base was limited by the high/unclear risk of bias of the studies and the low event rates for many outcomes. Conclusions: Oxycodone offers similar levels of pain relief and adverse events to other strong opioids. However, hallucinations occurred less with CR oxycodone than with CR morphine, but the quality of this evidence was very low, so this finding should be treated with utmost caution. Our conclusions are consistent with other reviews and suggest that oxycodone can be used first line as an alternative to morphine. However, because it is cheaper, morphine generally remains the first-line opioid of choice.